Some Immunological and Cytological Aspects .of The Breast and Uterus Can.cer Patients After Radiotherapy - Abid, A. AL.J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The- role of radiotherapy in immunological and  cytological function of  patients.  with  carcino.ma  of  breast 'tDd   uterus  were  investigared: Using n:>sette forming T lYJi'lphl)Cytes, white  blood  cell's and lymphocytes  count  and  distributiQn  of  micronuclei  as  parameters . After  irradiation . the number  of  peripheral   blood  lymphocytes and vvhite blood  cells  was  reduced  . The  percentage of ro:sette Jorming  Tly mphocytes   wereÂ· alsu  decreased   while  NBT  percentage  Of polymorpho  nudcocytes  were  increased  with  radiqtherapy  .  PeripheraJ blood  lymphocytes appears iridifferent fonnÂ·s  andshows fOrmation of micronuclei . The  nwnher  of n_,_icronuclci was sÂ·i_gnificantly  increased with  irradiation {!SJfecially  in  binuclear lymphocytes compared  v dth that before  irradiiltlon  .